2020
DOI: 10.1177/0976399620952354
|View full text |Cite
|
Sign up to set email alerts
|

Corona Pandemic and Stock Market Behaviour: Empirical Insights from Selected Asian Countries

Abstract: On the onset of the year 2020, the unprecedented outbreak of novel coronavirus, initially as a human health epidemic and later as a global pandemic, has wobbled the economies of affected countries across the globe. The consequential unexpected occurrences of supply- and demand-side shocks forced the economies to trim down their growth prospects. The interplay of these shocks has generated spirals of downturns in all major economic sectors, including the financial sector in affected countries. Specifically, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 42 publications
6
46
1
2
Order By: Relevance
“…Topcu and Gulal (2020) studied the impact of COVID-19 on emerging markets and found that Asian stock markets were more severely affected than European emerging markets. COVID-19 appalled the stock markets significantly compared to economic events such as GST implementation and demonetization in India (Mishra et al, 2020). All the above significant findings pave the way to further introspection of the methods that can be adopted for measuring and comparing the effect of COVID-19 on stock markets.…”
Section: Covid-19 and Stock Marketsmentioning
confidence: 88%
See 3 more Smart Citations
“…Topcu and Gulal (2020) studied the impact of COVID-19 on emerging markets and found that Asian stock markets were more severely affected than European emerging markets. COVID-19 appalled the stock markets significantly compared to economic events such as GST implementation and demonetization in India (Mishra et al, 2020). All the above significant findings pave the way to further introspection of the methods that can be adopted for measuring and comparing the effect of COVID-19 on stock markets.…”
Section: Covid-19 and Stock Marketsmentioning
confidence: 88%
“…Traces from the literature provide insight into an event study being majorly used to capture the im-pact of unsystematic risk and its deep-down effect on the individual stocks and industries Lyócsa & Molnár, 2020;Mishra et al, 2020). A sufficient count of previous studies focusing on the cross-country comparison of stock markets' reactions to COVID-19 (David et al, 2021;Mishra & Mishra, 2020;Topcu & Gulal, 2020) imitates the appropriateness of the event study method. Deficient documentation in the research wits shoves the path to measure and analyze the impact of macro events such as COVID-19 on the G-7 and BRICS nations, which propounds the idea of this study.…”
Section: G-7 Vs Bricsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of [13] stated that gold is a substantial safe haven against oil prices. Moreover, [14] stated that COVID-19 cases and oil prices changes directly affect the Asian stock markets. Consequently, it becomes essential to evaluate the impact of COVID-19 news on the variance and mean returns of WTI.…”
Section: Introductionmentioning
confidence: 99%